1998
DOI: 10.1046/j.1365-2133.1998.02418.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal pemphigus vulgaris associated with mild oral pemphigus vulgaris in the mother during pregnancy

Abstract: We report a neonate with immunofluorescence-proven pemphigus vulgaris. The condition presented at birth with widespread skin erosions and ulceration of the oral mucosa. Histopathological and immunofluorescence studies confirmed pemphigus vulgaris. The mother had mild oral pemphigus vulgaris treated during pregnancy with topical corticosteroids. All the neonate's skin erosions had crust formation at day 2 but healed completely within 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
0
39
1
Order By: Relevance
“…1,3,4 However, there is no clear correlation between the severity and pattern of maternal involvement, level of antibody titers or prematurity, and the neonatal clinical presentation. 5 Of note, in some cases of neonatal pemphigus, 3,4 including our case, DIF is positive for IgG and C3.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1,3,4 However, there is no clear correlation between the severity and pattern of maternal involvement, level of antibody titers or prematurity, and the neonatal clinical presentation. 5 Of note, in some cases of neonatal pemphigus, 3,4 including our case, DIF is positive for IgG and C3.…”
Section: Discussionmentioning
confidence: 91%
“…In previously reported cases, the infants' skin lesions completely healed within a few weeks of delivery. [4][5][6] However, if a pregnant woman is known to have pemphigus vulgaris, therapy during pregnancy should be aimed at reducing the antibody titer to lower the risk of transmission to the neonate. The most commonly used therapy is oral prednisone, but a recent report 7 showed that intravenous immunoglobulin administered at 4-week intervals throughout the pregnancy may be safe and effective.…”
Section: Discussionmentioning
confidence: 98%
“…Affected infants' skin disease resolves within weeks and may require treatment with topical antibiotics, topical corticosteroids, or supportive care only with bland emollients. 95,102 Ruach et al 96 suggest that conception be timed during a period of clinical remission with low immunofluorescence titers. The authors also recommend fetal screening with surveillance sonography, fetal movement counting, and repeat nonstress tests during the latter period of pregnancy.…”
Section: What Are the Differences Between Pemphigus Vulgaris In Childmentioning
confidence: 98%
“…100, 101 Antibody titers in the mother have ranged from 1:20 to 1:640 and several authors suggest that neither the antibody titers nor clinical severity of the mother's findings predict the severity of disease in the child. 99,102,103 All of the cases of intrauterine fetal death and growth retardation have been described in mothers with severe clinical disease. 96 This finding suggests that pathogenesis is multifactorial and that too few cases have been described to predict fetal outcome.…”
Section: What Are the Differences Between Pemphigus Vulgaris In Childmentioning
confidence: 98%
“…Two patients have been described in the literature, including 1 patient who developed EBA on day 2 post partum, with resolution of blistering at menopause, 25 and 1 patient who had a relapse of her EBA during the first month of gestation, with marked improvement of her skin following termination of the pregnancy. 26 As far as we know, congenital EBA has not been reported previously, likely because EBA itself is an extremely rare disorder. Experience with neonatal pemphigus has shown that such vertically transmitted autoimmune blistering disease appears to be selflimited and resolves with supportive therapy.…”
Section: Report Of a Casementioning
confidence: 99%